Response to SARS-CoV-2 initial series and additional dose vaccine in pediatric patients with predominantly antibody deficiency - Tandon, Megha; DiGiacomo, Daniel V.; Zhou, Baijun; Hesterberg, Paul; Rosenberg, Chen E.; Barmettler, Sara; Farmer, Jocelyn R. (Frontiers in Immunology, 2023)
Data regarding response to SARS-CoV-2 immunization in pediatric patients with predominantly antibody deficiency (PAD) is limited. We evaluated SARS-CoV-2 immunization response by anti-SARS-CoV-2-spike antibody level in 15 pediatric PAD patients. These data were compared to a published cohort of adult PAD patients (n=62) previously analyzed following SARS-CoV-2 immunization at our single center institution. We evaluated demographics, clinical characteristics, immunophenotype, infection history, and past medication use by chart review. Following a two-dose monovalent initial series SARS-CoV-2 immunization, mean anti-SARS-CoV-2-spike antibody levels were significantly higher in pediatric PAD patients compared to adult PAD patients (2,890.7 vs. 140.1 U/mL; p<0.0001). Pediatric PAD patients with low class-switched memory B-cells, defined as <2% of total CD19+ B-cells, had significantly lower mean anti-SARS-CoV-2-spike antibody levels than those without (p=0.02). Following a third-dose monovalent SARS-CoV-2 immunization, the mean anti-SARS-CoV-2-spike antibody levels in pediatric PAD patients significantly increased (2,890.7 to 18,267.2 U/mL; p<0.0001). These data support Centers for Disease Control guidelines regarding three-part SARS-CoV-2 vaccine series, including in the pediatric PAD patient demographic.